Милая мятежница: роман / Констанс Холл ; [перевод с английского А. П. Кашина] - Холл Констанс (Шарм, 2003)
Экземпляры: ф.22 (2003) / Инвентарный номер: 46609 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Х 72 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44